Antidiabetic Drugs as Antihypertensives: New Data on the Horizon - Mamakou, Vassiliki; Eleftheriadou, Ioanna; Katsiki, Niki; Makrilakis, Konstantinos; Tsioufis, Konstantinos; Tentolouris, Nikolaos (Current Vascular Pharmacology, 2018)
Background: The prevalence of Type 2 Diabetes Mellitus (T2DM) is increasing worldwide; this is stimulating more research into the optimal management of this disease. Cardiovascular Disease (CVD) remains the commonest cause of death in individuals with T2DM. Besides hyperglycaemia, an explanation for the increased mortality in this population is the increased prevalence of comorbidities, such as hypertension and dyslipidaemia. Recent population-based studies described a prevalence of hypertension >80% in patients with T2DM. In the last decade new classes of antidiabetic medications have been developed that are effective not only for the management of hyperglycaemia and but also for tailoring treatment according to individual needs and characteristics. Regulatory authorities demand the new antidiabetic medications to be examined for Cardiovascular (CV) safety. Interestingly it has been shown, mainly through CV safety trials, that some new antidiabetic medications not only have glucose lowering effects, but also Blood Pressure (BP) lowering effects, contributing to CV risk reduction. Conclusion: This review considers the effect of older and newer antidiabetic medications on BP in patients with T2DM.
Keywords: antidiabetic medications